CENTRAL NERVOUS SYSTEM TUBERCULOSIS- CASE REPORT CASE REPORT - Cepreganova Cangovska, Tatjana; Zdravkov, Ilija; Aleksovska, Angela; Ristic-Stomnaroska, Daniela; Joveva, Elena (Journal of Morphological Sciences, 2023)
Mycobacterium tuberculosis is the leading cause of morbidity and mortality worldwide. Tuberculosis is the second most common cause of death due to an infectious agent worldwide after COVID-19 infection. Central nervous system tuberculosis (CNS-TB), accounts for approximately 1% of all cases of tuberculosis, and the most common clinical presentation is tuberculous meningitis (TBM). Tuberculosis of the central nervous system is a devastating disease that, even under appropriate antituberculin therapy, leads to high mortality rate. In this paper we present a case report of a patient in whom the disease begins slowly, progressively and chronically, with the initial clinical manifestation of dementia syndrome. Usually, TBM presents with a subacute progressive febrile illness. In 2 to 3 weeks defines meningitis phase with headache, meningismus, vomiting, mild confusion. Rare is the atypical presentation of CNS TB, as in our case. During the hospitalization, brain magnetic resonance was performed with suspicious finding for neuroinfection, Due to the suspected finding of magnetic resonance imaging, a lumbar puncture was performed and the cerebrospinal fluid was sent for analysis for specific causes, including Mycobacterium tuberculosis. Correct diagnosis and therapy in these patients are a challenge for neurologists. Key words: central nervous system tuberculosis, mycobacterium tuberculosis, neuroinfection.